Within batch non-linear profile monitoring applied to shrimp farming: A case study - Quevedo A.V. (2020)
The operation of many batch processes involves critical characteristics that follow specific patterns over time. Sometimes the batch time is long enough that the operator can take corrective actions within it. This paper explores how to develop appropriate monitoring procedures for such situations within the context of a shrimp farming process. It uses a Gompetz non-linear model to describe the basic shrimp growth and defines the control limits through the prediction band around the estimated model. It proposes a method to generate a control chart soon enough within the batch so management can prioritize which ponds require the most attention. © 2021 Taylor & Francis Group, LLC.